Internet-scale pattern recognition new techniques for voluminous data sets and data clouds - Muhamad Amin, Anang Hudaya (2013)
"This cutting-edge reference outlines the underlying theory and principles of efficient and effective distributed pattern recognition involving one-shot learning and in-network processing for different types of applications, including multimedia retrieval systems and event detection over different network environments. Investigating one-shot learning and in-network processing as complementary mechanisms for efficient and accurate distributed pattern analyses, it presents the technical aspects related to the development of scalable pattern recognition using a number of contemporary application development tools. It also considers scalability of pattern recognition schemes when dealing with such data"--
Includes bibliographical references and index. - Print version record
Keywords: Data mining; Pattern recognition systems; Web usage mining; Mathematical statistics -- Data processing; Exploration de données (Informatique); Reconnaissance des formes (Informatique); Analyse du comportement des internautes; Statistique mathématique; Informatique; COMPUTERS; Database Management; Data Mining; COMPUTERS; Machine Theory; COMPUTERS; Internet; General; Mathematical statistics; Data processing